THE EFFECT OF COOPERATIVE LEARNING TYPE TERROR CARDS AND NIGHTMARE CARDS TOWARDS THE ELEVENTH GRADE STUDENTSâ SPEAKING - Hendrawati, Enda (IKIP Mataram, 2018)
This research aimed to find out the effect of cooperative learning type terror cards and nightmare cards towards studentsâ speaking skill at SMAN 1 Sakra Timur in academic year 2017/2018. The research was pre-experimental with one-shot case study design. The population of the study was the eleventh grade students of SMAN 1 Sakra Timur that consisted of 3 classes. All of classes were chosen as the samples, those were XI IPS 1 as experimental group I, XI IPS 2 as experimental group II and XI IPS 3 as control group. They were chosen by using total sampling technique. Experimental group I treated by using terror cards, experimental group II treated by using nightmare cards, and control group treated by using think pair share. The data of the research were gathered from speaking test and the data analysis used ANOVA. Based on the data analysis was gotten F-test = 3.352 and F-table = 2.44. It means that f-test was higher than f-table (3.352 > 2.44) with signification level 0.04. So that way, alternative hypothesis (Ha) accepted and null hypothesis (Ho) rejected. Therefore, it took conclusion that there is significant effect of cooperative learning toward students speaking skill at SMAN 1 Sakra Timur in academic year 2017/2018.